Mit jelent a hazát szeretni és együtt menetelni minden testvérünkkel? . What does it mean to love our homeland and march with our brothers? (Magyar Diafilmgyártó Vállalat, 1962)
Produced for the Central Committee of the Communist Youth Association, Department for Agitation and Propaganda.